2021
DOI: 10.26529/cepsj.1147
|View full text |Cite
|
Sign up to set email alerts
|

Higher Education Students’ Experience of Emergency Remote Teaching during the Covid-19 Pandemic in Relation to Self-Regulation and Positivity

Abstract: The main objective of the present research was to explore students’ experiences of emergency remote teaching during the Covid-19 pandemic. Specifically, we were interested in how strategies for coping with an emergency situation, learning strategies and positivity relate to this experience. A total of 337 university students participated in the study. The data were collected with an online questionnaire. The results show that students used more adaptive coping strategies (positive reappraisal, acceptance and r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
5
0
3
Order By: Relevance
“…Lack of Human Interaction. Twelve studies revealed that students lacked human interaction and felt disconnected from lecturers and friends during ERTL (Abubakar et al, 2022;Alvarez, 2020;Basri et al, 2022;Dvorakova et al, 2021;Edmond et al, 2020;Egan & Crotty, 2020;Gqokonqana et al, 2022;Jurisˇevicˇet al, 2021;Korkmaz & Toraman, 2021;Lewis et al, 2021;Steinberger et al, 2021;Wilcox & Vignal, 2020). In addition, Gelles et al (2020) reported that students experienced miscommunication during ERTL.…”
Section: Social Presencementioning
confidence: 99%
“…Lack of Human Interaction. Twelve studies revealed that students lacked human interaction and felt disconnected from lecturers and friends during ERTL (Abubakar et al, 2022;Alvarez, 2020;Basri et al, 2022;Dvorakova et al, 2021;Edmond et al, 2020;Egan & Crotty, 2020;Gqokonqana et al, 2022;Jurisˇevicˇet al, 2021;Korkmaz & Toraman, 2021;Lewis et al, 2021;Steinberger et al, 2021;Wilcox & Vignal, 2020). In addition, Gelles et al (2020) reported that students experienced miscommunication during ERTL.…”
Section: Social Presencementioning
confidence: 99%
“…A análise das pesquisas incluídas na presente revisão permite identificar que, de maneira geral, o uso de estratégias de aprendizagem por estudantes de cursos de licenciatura, nos últimos seis anos, tem sido moderado tanto em situações de ensino presencial como de ensino remoto emergencial, causado pela pandemia de Covid-19 (ARCOVERDE et al, 2022;BOOM, 2020;LIU et al, 2019;JURIŠEVIČ et al, 2021;ÖZDEMIR;ÖNAL, 2021). Não obstante, observa-se que o uso de estratégias não é homogêneo entre esses estudantes, podendo-se identificar grupos distintos quanto ao seu uso (HÄKKINEN et al, 2020;REINDL;TULIS;DRESEL, 2020;MUWONGE et al, 2020).…”
Section: Introductionunclassified
“…É possível identificar que o emprego de algumas estratégias, como as cognitivas de ensaio e as metacognitivas de gerenciamento do ambiente de estudo e de estabelecimento de metas, é mais frequente do que o de outras, como as cognitivas de elaboração e as metacognitivas de autoavaliação, planejamento, preparação para testes e provas e de gerenciamento da motivação e emoções (ARCOVERDE et al, 2022;BORUCHOVITCH et al, 2020;DIAS et al, 2021;JURIŠEVIČ et al, 2021;KÖRÜKCÜ, 2020;LIU et al, 2019;VOSNIADOU et al, 2021). Apesar de todas as estratégias terem sua importância e momentos indicados para seu uso, é fundamental que os estudantes, sobretudo aqueles que aspiram a ser professores, tenham maior conhecimento declarativo e condicional sobre o uso das estratégias cognitivas profundas e das estratégias metacognitivas (GÓES; BORUCHOVITCH, 2020; WEINSTEIN; ACEE, 2018).…”
Section: Introductionunclassified
“…),Juriševič et al (2021),Ferri, Grifoni, Guzzo (2020),Fuchs (2021) eLi et al (2021) salientam que no ensino remoto existe flexibilização das aulas, assim comoGherheș et al (2021),Islam, Nur, Talukder (2021) eSouza et al (2021) acreditam que a diminuição das despesas e de tempo é uma vantagem dessa modalidade de ensino.Constata-se que em relação ao Ensino Remoto estimular a inovação /criatividade dos discentes, 37,70% concordam com essa assertiva, mas quase 20% discordam e aproximadamente um quarto dos respondentes nem discordam e nem concordam. Já no que tange ao Ensino Remoto como um estímulo à autonomia do aluno, 45,90% concordam com a questão________________________________________________________________________________ Perspectivas em Diálogo, Naviraí, v. 10, n. 25, p. 242-266, out/dez.…”
unclassified